Designing A New Fuzzy Expert System for Project Portfolio Risk Management - Masoumeh Zahedi; Mohamad Khalilzadeh; Hasan Javanshir (مدیریت نوآوری و راهبردهای عملیاتی, 2021)
Purpose: This study aimed to design a new fuzzy expert system for project portfolio risk management in ongoing projects of a first mobile holding. Methodology: To identify the risks from the DEMATEL method developed, to evaluate and determine the most critical risks from the fuzzy FMEA methods and the AHP method in Expert Choice software, and to select the optimal risk response, a proposed mathematical model is used and solved in Gamz software. Findings: The research findings showed 23 risks in the studied projects, 8 of which were highly important and impacted. Risk prioritization and determining their impact level were also performed using the integrated AHP-FMEA method. Findings obtained from solving and implementing the mathematical model in Gamz software also showed that the proposed model of efficiency and capability for selecting optimal risk response strategies is established. Originality/Value: The general findings indicate that the proposed new fuzzy expert system also has the capability and efficiency to manage the portfolio risk in the study holding.